The effect of transverse bending on the dispersion curves of multi layered metal loaded waveguides - Ojha S.P.; Choudhury P.K.; Khastgir P. (My University, 2025)
We present a study of the dispersion curves of a four-layer metalloaded waveguide (FLMW) which is bent across the direction of propagation. The bending of the waveguide referred to may arise naturally owing to manufacturing defects and the effect of environment, The curvature of the waveguide is so small that the asymptotic field solutions can be used to study the propagation characteristics. Considering a step-index profile and making use of the scalar wave equation, we obtain the dispersion curves of an FLMW for a large number of modes and an interesting mode proliferation property of this waveguide is noticed. Using the same phenomenon, the dispersion curves for a fourlayer metal loaded planar waveguide (FLPW) are also presented. A comparative study of the modal characteristics of FLMW and FLPW yields that the FLMW shows the mode-proliferation aspect whereas the FLPW lacks this interesting feature. Therefore, this proliferation may be attributed to the bending of the waveguide. © 1993 Proceedings of SPIE - The International Society for Optical Engineering. All rights reserved.